ECONOMIC INSTITUTIONS THROUGH VILLAGE-OWNED ENTERPRISE IN DEVELOPING COUNTRIES - Pardi, Pardi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to analyze the institutional organization of Village – Owned Enterprise through community empowerment and the role of Village – Owned Enterprise as a “law of village administration” or the economic activities of the enterprise in community empowerment. This research uses qualitative approach, with subjective and historical information, and case study strategy. The data are obtained by observation, documentation, physical device, and data transcription analysis. The data are organized, identified, coded, and validated using triangulation technique. The result of this research shows that the economic institutional organization benefits the business units, so it increases the community income.Village – Owned Enterprise functions like a “law of village administration” so it is able to support the village authority in achieving the prosperity of its people. Keywords: Economic Institutions, Village – Owned Enterprise